Assessing contraceptive use and its impact on population control in Nigeria (2017)
Labour disputes in Nigeria have assumed such fervent dimension that there arose the dire need to arrest situations arising therefrom, or, as an alternative, watch the entire governmental and economic system crumble. The need to provide forum for the resolution of labour related disputes call for both legislative and judicial interventions to tame the rising trends in the 1970s. Part of the legislative intervention at the time was the establishment of the National Industrial Court of Nigeria as a special court with jurisdiction to entertain trade and labour related disputes. The court was further given power to make rules for its operation and to guide proceedings before it. To this end, the court recently enacted another set of Rules, which repealed the 2007 Civil Procedures Rules of the court. The thrust of this paper is to analysis the rules, practice and procedure of National Industrial Court in labour disputes in Nigeria. The objective is to sensitize and appraise litigants on the rules, practice and procedures of the court and how best to harness them in the resolution of labour disputes. The paper concludes with suggestions that will promote effective administration of justice in labour related disputes in Nigeria.